Women and Livelihood Resilience of Household: Analysis of Oil Palm Expansion Impact in Jambi - Azzahra, Fatimah; Hadi Dharmawan, Arya; K. Pandjaitan, Nurmala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTIndonesia is the greatest producer of oil palm in the world. Despite providing economic benefits, oil palm plantations cause significant environmental and social impacts. Environmental impacts such as deforestation, loss of biodiversity, forest fires and drought. The social impact of oil palm expansion changes women works in livelihood resilience. The purpose of this study are to analyze the influence of oil palm plantations to the livelihood structure and working changes in women and men at smallholder household in Jambi. The method used is mix method using questionnaire and in-depth interviews. The results are the expansion of oil palm plantations cause structural changes such as the shift subsistence living from rubber plantations into oil palm plantation and on lower household changes women from domestic work into the public work as oil palm labours. This is done to increase income of the household in order to remain economically resilient when a crisis situation. However, the environment is very vulnerable, causing drought and exacerbated by forest firesKeywords: oil palm, livelihood, women, resilience, householdABSTRAKIndonesia merupakan negara produsen minyak kelapa sawit terbesar di dunia. Meskipun memberikan manfaat ekonomi, perkebunan kelapa sawit menimbulkan dampak lingkungan dan sosial yang signifikan. Dampak lingkungan seperti deforestasi, hilangnya keanekaragaman hayati, hingga bencana kebakaran hutan dan kekeringan. Dampak sosial perkebunan kelapa sawit yaitu mengubah pekerjaan perempuan dalam resiliensi nafkah. Tujuan dari penelitian ini yaitu menganalisis sejauh mana ekspansi perkebunan kelapa sawit mempengaruhi struktur nafkah dan kerja nafkah laki-laki dan perempuan pada rumahtangga petani di Provinsi Jambi. Metode yang digunakan yaitu metode campuran dengan menggunakan kuesioner dan wawancara mendalam. Hasil penelitian ini yaitu ekspansi perkebunan kelapa sawit menyebabkan perubahan struktur nafkah berupa pergeseran sumber nafkah dari perkebunan karet menjadi perkebunan kelapa sawit. Selain itu, pada rumahtangga lapisan bawah terjadi perubahan kerja perempuan dari domestic menjadi ke ranah publik yaitu sebagai buruh kelapa sawit. Hal tersebut dilakukan untuk menambah penerimaan rumahtangga agar tetap resilien secara ekonomi ketika terjadi krisis. Namun, lingkungan menjadi sangat rentan sehingga menimbulkan kekeringan dan diperparah dengan kebakaran hutan.Kata kunci: kelapa sawit, nafkah, perempuan, resiliensi, rumahtangga